Regeneration of Quercus Spp. Along Interactive Forest Boundaries in a Fragmented Peri-Urban Landscape of Mexico City - Vergara-Egert, P (Cambridge University Press, 2020)
Biodiversity conservation in forest fragments surrounded by a low-quality matrix requires an understanding of how ecological conditions prevailing in the matrix enter the fragments and interact with local habitat conditions. We assessed the regeneration of oak species along edge-interior gradients in forest fragments at the periphery of Mexico City. The abundance of oak saplings was sampled along transects to the forest, while the edge effect was analysed using segmented zero-inflated Poisson models for abundance data. Three oak species were dominant in terms of their relative abundances: Quercus laeta, Quercus castanea and Quercus obtusata. Regeneration of nine oak species responded nonlinearly to the edge distance, with greater sapling abundance from the edge up to 10 m into the fragment. Canopy cover and tree height decreased from edge to fragment interior, while saplings increased in open areas within the fragments (i.e., independent of edge distance). A posterior analysis indicated that Q. obtusata reacted positively to edges. These results indicate that oak regeneration is promoted by suitable habitat conditions near the boundaries. Therefore, we suggest that forest management should focus on promoting seed production and oak establishment in forest interior habitats. © Foundation for Environmental Conservation 2019.